Boy in the Striped Pyjamas - John Boyne (London Vintage Books, 2006)
Discover an extraordinary tale of innocence, friendship and the horrors of war. 'Some things are just sitting there, minding their own business, waiting to be discovered.
Keywords: English Fiction; English Literature